Multi-attribute evaluation and deviation analysis of regional distribution network investment effect - Wu Jianbin; Wang Zheng; Gu Zhihong; Liu Zhuo (E3S Web of Conferences, 2020)
As the input ratio of regional distribution network increases year by year, higher requirements are put forward for high quality and high reliability of power consumption. Under this background, this paper involves 11 evaluation indexes from three dimensions of reliability, economy and environmental protection, and designs the evaluation index system of investment effect of regional distribution network. The multiattribute AHP-TOPSIS-entropy weight combination evaluation method for the investment effect of regional distribution networks is constructed. And select distribution network A, B, C area for example analysis, the results show that the n-1 pass rate, power supply reliability, power consumption growth and emission reduction of clean energy generation are positively correlated with the investment effect of regional distribution network.